Cathodoluminescence of nitrogen-containing diamond samples at temperatures of 80–800 K - Burachenko, Alexander G.; Ripenko, Vasilii S.; Lipatov, Evgeniy I.; Artyomov, Konstantin P.; Krylov, A. A. (Russian physics journal)
The spectral characteristics of the cathodoluminescence of several synthetic nitrogen-containing diamond samples excited by an electron beam with an energy of up to 300 keV in the temperature range of 80–800 K are studied. The data on temperature quenching of the cathodoluminescence of diamond samples with differing impurity-defect compositions at elevated temperatures (more than 400 K) are obtained. It is found out that the rate of thermal quenching of NV0 centers is higher than that of NV–centers at the temperatures of ~500 K and higher.